"Machiavellian" Instruction: Why Hesiod's Ainos Has No Moral. Issue 6 (18th August 2017) - O'Mahoney, Paul
Abstract: Hesiod's fable ( ainos ) of the hawk and the nightingale, addressed to kings, notoriously has no moral. Its depiction of a hawk carrying off a nightingale, preaching the futility of either resistance or pleading, appears to communicate the counsel, commonly designated as "Machiavellian, " that a ruler must know how to imitate a beast as well as a man. Such instruction—which advises that unjust actions are justifiable and necessary for a ruler—is clearly at odds with Hesiod's explicit exhortations to his brother Perses to work hard and avoid hubris, and his caution that unjust kings or lords ( basileis ) will be punished by Zeus. I argue that Hesiod's addressing the fable to kings "who themselves have understanding" explains the lack of a moral. To substantiate my claim I compare Hesiod's and Machiavelli's ranking of intellects, and illuminate Hesiod's position with particular reference to and comparison with Machiavelli's Prince, and examples drawn from the Old Testament and Old Irish law.